PLURALISME: STUDI ATAS PEMIKIRAN, SIKAP DAN TINDAKAN GUS DUR DALAM BUKU â€œISLAMKU, ISLAM ANDA, ISLAM KITAâ€ - Masyhud masyhud (IAIN Purwokerto, 2016)
Abstract: Gus Dur is son of a great kiai, grandson of K.H. Hasyim Ashari, caretaker of Pondok Pesantren Tebuireng and son of former Minister of Religious Affairs in the cabinet of Sukarno. He is a controversial and eccentric figure. Gus Dur asralism figure capable of flapping wings in five fields at once; religion, democracy, ideology, culture, and politics. Frequently his attitudes and actions confuse great kiais. Moreover, his students as a large part of the community based nahdliyyin stress, unable to understand his flow of thought and action. When Gus Dur became president, he appearing on the front line to teach the people of Indonesia for practicing